Ethnic Activism and Civil Society in South Asia (Governance, Conflict, and Civic Action 2) - Gellner, D (SAGE Publications, 2009)
Includes 'Introduction: How Civil are 'Communal' and Ethno-Nationalist Movements' (pp 1-24)